2019
DOI: 10.1002/ana.25566
|View full text |Cite
|
Sign up to set email alerts
|

Imaging gradual neurodegeneration in a basal ganglia model disease

Abstract: ObjectiveX‐linked dystonia‐parkinsonism (XDP) is a neurodegenerative disease with adult onset dystonia and subsequent parkinsonism. Postmortem and imaging studies revealed remarkable striatal pathology, with a predominant involvement of the striosomal compartment in the early phase. Here, we aimed to disentangle sequential neurodegeneration in the striatum of XDP patients, provide evidence for preferential loss of distinct striatal areas in the early phase, and investigate whether iron accumulation is present.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 49 publications
7
39
0
Order By: Relevance
“…We show for the first time evidence of abnormally high levels of NfL in XDP plasma, reflecting a neurodegenerative process occurring in the brains of patients with XDP, but not in males with presymptomatic XDP or asymptomatic female carriers. Our results are consistent with the knowledge that XDP is a disease of basal ganglia neurodegeneration 1‐4,9 . This adds XDP to the list of atypical parkinsonian syndromes with increased plasma NfL 24,29,30 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We show for the first time evidence of abnormally high levels of NfL in XDP plasma, reflecting a neurodegenerative process occurring in the brains of patients with XDP, but not in males with presymptomatic XDP or asymptomatic female carriers. Our results are consistent with the knowledge that XDP is a disease of basal ganglia neurodegeneration 1‐4,9 . This adds XDP to the list of atypical parkinsonian syndromes with increased plasma NfL 24,29,30 …”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with the knowledge that XDP is a disease of basal ganglia neurodegeneration. [1][2][3][4]9 This adds XDP to the list of atypical parkinsonian syndromes with increased plasma NfL. 24,29,30 Although NfL may be a nonspecific biomarker of neurodegeneration in XDP, it may still be useful in monitoring disease onset and progression in presymptomatic and symptomatic patients under therapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggest that there is no apparent macroscopic degeneration or irregularity in the brain in isolated dystonia (Rostasy et al 2003;Paudel et al 2012Paudel et al , 2016. This is different in forms of dystonia with a neurodegenerative pattern, such as DYT/PARK-TAF1 (Hanssen et al 2019). Neuroimaging studies, on the other hand, have identified more subtle alterations, with respect to cortical thickness and gray matter volume differences in cortical regions, basal ganglia, thalamus, hippocampus, and amygdala in focal dystonia (Tomić et al 2020), as well as for the subthalamic area of the brain stem in myoclonus-dystonia (van der Meer et al 2012).…”
Section: Pathological Findings Of the Nervous System In Dystoniamentioning
confidence: 99%